Writing for games : theory and practice - Nicklin, Hannah (Boca Raton : CRC Press, 2022)
Focussing on the independent videogames sector, this book provides readers with a vocabulary to articulate and build their games writing practice; whether studying games or coming to games from another storytelling discipline. Writing for Games offers resources for communication, collaboration, reflection, and advocacy, inviting the reader to situate their practice in a centuries-long heritage of storytelling, as well as considering the material affordances of videogames, and the practical realities of working in game development processes. Structured into three parts, Theory considers the craft of both games and writing from a theoretical perspective, covering vocabulary for both game and story practices. Case Studies uses three case studies to explore the theory explored in Part 1. The Practical Workbook offers a series of provocations, tools and exercises that give the reader the means to refine and develop their writing, not just for now, but as a part of a life-long practice. Writing for Games: Theoryand Practice is an approachable and entry-level text for anyone interested in the craft of writing for videogames. Hannah Nicklin is an award-winning narrative and game designer, writer, and academic who has been practising for nearly 15 years. She works hard to create playful experiences that see people and make people feel seen, and also argues for making games a more radical space through mentoring, advocacy, and redefining process. Trained as a playwright, Nicklin moved into interactive practices early on in her career and is now the CEO and studio lead at Danish indie studio Die Gute Fabrik, which most recently launched Mutazione in 2019.
Introduction -- Part I: Theory. Chapter 1: Craft -- Chapter 2: Vocabulary: Games -- Chapter 3: Vocabulary: Story structure -- Chapter 4: Vocabulary: Story components -- Chapter 5: Games writing as a discipline -- Chapter 6: Form-led design -- Chapter 7: A note on writing comedy -- Chapter 8: Further reading -- Chapter 9: a note on ethics -- Part II: Case studies. Chapter 10: Introduction to the case studies -- Chapter 11: Character and dialogue in Life is Strange 2 -- Chapter 12: Ethics and adaptation in 80 Days -- Chapter 13: Format and the heist in Last Stop -- Part III: A practical workbook -- Chapter 14: Introduction to the workbook -- Chapter 15: Tools for starting -- Chapter 16: Tools for developing -- Chapter 17: Tools for finishing -- Conclusion
OCLC-licensed vendor bibliographic record.
Keywords: Video games -- Authorship; Video games -- Authorship -- Vocational guidance; Video games -- Design; Video games -- Design -- Vocational guidance; GAMES / General; GAMES / Role Playing & Fantasy; GAMES / Video & Electronic